The Role of Transformational Leadership, Intrinsic Motivation, and Job Satisfaction in Enhancing Employee Performance at the Regional Financial and Asset Management Agency Ternate City - Alhaddad, Salsha Raehana; Sabuhari, Rahmat; Arilaha, Muhammad Asril (Jurnal Manajemen Sinergi, 2024)
ABSTRACTObjective: This study aims to analyze the influence of transformational leadership, intrinsic motivation, and job satisfaction on employee performance in the public sector.Methodology: This research employs a survey design with a quantitative approach to analyze the effects of transformational leadership, intrinsic motivation, and job satisfaction on employee performance. Data were collected through a structured questionnaire from 88 civil servants at the Regional Financial Management and Asset Agency of Ternate City. Analysis was conducted using multiple linear regression with SPSS after conducting validity, reliability, linearity, multicollinearity, and heteroscedasticity tests. Hypotheses were tested using statistical t and F criteria.Findings: The analysis results indicate that transformational leadership has a significant impact on employee performance. Intrinsic motivation shows a regression coefficient of 0.550 with a t-statistic value of 4.986 and a significance level of 0.000. Job satisfaction also has a significant effect with a regression coefficient of 0.336, a t-statistic of 6.295, and a significance level of 0.000. The R Square value of 0.518 indicates that 51.8% of the variability in employee performance can be explained by these three variables.Conclusion: Transformational leadership, intrinsic motivation, and job satisfaction collectively contribute significantly to enhancing employee performance. This study suggests a need for greater attention to these factors to improve employee performance in the public sector. Further research is needed to explore other factors that may have an impact.Â